2023
DOI: 10.1111/imr.13182
|View full text |Cite
|
Sign up to set email alerts
|

Inside the phagosome: A bacterial perspective

Abstract: Summary The neutrophil phagosome is one of the most hostile environments that bacteria must face and overcome if they are to succeed as pathogens. Targeting bacterial defense mechanisms should lead to new therapies that assist neutrophils to kill pathogens, but this has not yet come to fruition. One of the limiting factors in this effort has been our incomplete knowledge of the complex biochemistry that occurs within the rapidly changing environment of the phagosome. The same compartmentalization that protects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 127 publications
(279 reference statements)
0
9
0
Order By: Relevance
“…After infection of the host, the pathogens are phagocytosed by the cells of our innate immune system, such as macrophages and neutrophils. The phagocytosis of the bacteria is associated with an oxidative burst of activated neutrophils, which is aimed to kill the invading bacteria ( 7 10 ). First, the NADPH oxidase is assembled in the phagosomal membrane, which transfers electrons to oxygen to produce reactive oxygen species (ROS), such as superoxide anions at concentrations of 2 mM/s ( 8 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…After infection of the host, the pathogens are phagocytosed by the cells of our innate immune system, such as macrophages and neutrophils. The phagocytosis of the bacteria is associated with an oxidative burst of activated neutrophils, which is aimed to kill the invading bacteria ( 7 10 ). First, the NADPH oxidase is assembled in the phagosomal membrane, which transfers electrons to oxygen to produce reactive oxygen species (ROS), such as superoxide anions at concentrations of 2 mM/s ( 8 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed discussion of how bacteria affect the phagosomal environment is reviewed elsewhere in this issue. 143 The fate of protein chloramines is intriguing because they account for a large proportion of hypochlorous acid generated in the phagosome. We have shown that protein dichloramines breakdown to release bactericidal monochloramine gas (NH 2 Cl).…”
Section: Spontaneous Dismutation Of Superoxide (Reaction 7) Is Minimalmentioning
confidence: 99%
“…To be maximally effective in neutrophil phagosomes, SPIN would have to be present at a similar concentration to that of myeloperoxidase. A more detailed discussion of how bacteria affect the phagosomal environment is reviewed elsewhere in this issue 143 …”
Section: Kinetic Modelling Of Superoxide's Reactions Inside Phagosomesmentioning
confidence: 99%
“…Capitalizing on skills refined by their adaptations to threats from competing organisms in environmental settings, microbes are not passive victims trapped in phagosomes but rather targets that sense and react to the hostile conditions encountered. Hampton and Dickerhof 12 discuss how microbes can actively undermine neutrophil responses, change surface charge to rebuff attack by cationic antimicrobial peptides, release agents that bind and inactivate antimicrobial mediators (as occurs with MPO inactivation by the staphylococcal peroxidase inhibitor, SPIN), degrade or neutralize oxidants, and repair damage exerted by phagosomal contents. The speed with which organisms adapt to their new environments can be remarkable and, when successful, allow ingested bacteria to persist, alive, within neutrophils.…”
Section: Life and Death In The Phagosomementioning
confidence: 99%
“…Whereas the complex mix of interacting agents within phagosomes and the capacity of ingested microbes to counter the attack together make deciphering how neutrophils kill microbes nearly impossible, the heterogeneity among phagosomes compounds the challenge even further. As reviewed by Hampton and Dickerhof, 12 not all neutrophils in circulation exhibit the same capacity for phagocytosis and, even within the same neutrophil, phagosomes differ with respect to their capacity to generate oxidants. The challenges to understanding fully the most fundamental aspect of phagocyte biology, i.e., killing ingested microbes, seem insurmountable.…”
Section: Life and Death In The Phagosomementioning
confidence: 99%